Contemporaneous X-Ray Observations of 30 Bright Radio Bursts from the Prolific Fast Radio Burst Source FRB 20220912A - Amanda M. Cook; Paul Scholz; Aaron B. Pearlman; Thomas C. Abbott; Marilyn Cruces; B. M. Gaensler; Fengqiu Adam Dong; Daniele Michilli; Gwendolyn Eadie; Victoria M. Kaspi; Ingrid Stairs; Chia Min Tan; et al. (The Astrophysical Journal, 2024)
We present an extensive contemporaneous X-ray and radio campaign performed on the repeating fast radio burst (FRB) source FRB 20220912A for 8 weeks immediately following the source’s detection by CHIME/FRB. This includes X-ray data from XMM-Newton, NICER, and Swift, and radio detections of FRB 20220912A from CHIME/Pulsar and Effelsberg. We detect no significant X-ray emission at the time of 30 radio bursts with upper limits on a 0.5–10.0 keV X-ray fluence of (1.5–14.5) × 10 ^−10 erg cm ^−2 (99.7% credible interval, unabsorbed) on a timescale of 100 ms. Translated into a fluence ratio η _x/r = F _X-ray / F _radio , this corresponds to η _x/r < 7 × 10 ^6 . For persistent emission from the location of FRB 20220912A, we derive a 99.7% 0.5–10.0 keV isotropic flux limit of 8.8 × 10 ^−15 erg cm ^−2 s ^−1 (unabsorbed) or an isotropic luminosity limit of 1.4 × 10 ^41 erg s ^−1 at a distance of 362.4 Mpc. We derive a hierarchical extension to the standard Bayesian treatment of low-count and background-contaminated X-ray data, which allows the robust combination of multiple observations. This methodology allows us to place the best (lowest) 99.7% credible interval upper limit on an FRB η _x/r to date, η _x/r < 2 × 10 ^6 , assuming that all 30 detected radio bursts are associated with X-ray bursts with the same fluence ratio. If we instead adopt an X-ray spectrum similar to the X-ray burst observed contemporaneously with FRB-like emission from the Galactic magnetar SGR 1935+2154 detected on 2020 April 28, we derive a 99.7% credible interval upper limit on η _x/r of 8 × 10 ^5 , which is only 3 times the observed value of η _x/r for SGR 1935+2154.